(untitled) (Bangladesh Journal of Botany, 2014)
The total caffeine content in Bangladesh Tea (BT) varieties (BT1-BT18) ranged from 1.59 ± 0.155 - 4.15 ± 0.399 g/100g of DM and the crude fat content in BT varieties varied from 6.69 ± 0.64 - 9.87 ± 0.9509 g/100g of dry material (DM). In this study, the highest amount of caffeine (4.15 ± 0.399 g/100g DM) was found in BT-16 variety (p < 0.05) while the highest amount of crude fat (9.24 ± 0.889g/100g DM) was found in BT 10 variety (p > 0.5). The total polyphenol content ranged:8.66 ± 0.831 - 14.89 ± 1.432 GAE; g/100 g DM. The highest amount of polyphenol was found in BT 9 variety (14.890 ± 1.432 GAE; g/100 g DM) (p < 0.05). DOI: http://dx.doi.org/10.3329/bjb.v42i2.18037 Bangladesh J. Bot. 42(2): 321-325, 2013 (December)